Predictors of pathologic response to neoadjuvant chemotherapy in muscle-invasive bladder cancer - Sainont, Gantapong; Santingamkun, Apirak; Ratchanon, Supoj; Opanurak, Julin; Panumatrassamee, Kamol; Sowanthip, Dutsadee (Insight Urology, 2022)
Objective: To identify factors that could predict pathologic response to neoadjuvant (NAC) therapy in muscle invasive bladder cancer (MIBC) patients and report the impact of NAC on the risk of perioperative complications after radical cystectomy at our institution. Materials and Methods: We reviewed the hospital database from January 2014 to March 2021 for MIBC patients who received NAC prior to radical cystectomy (RC). All patients were divided into a responder (pT ≤ T1) or non-responder group (> pT2). Data was analyzed to determine the factors associated with pathologic response to NAC. A subgroup analysis of the gemcitabine and carboplatin (GCb) regimens was also carried out. Results: Out of the 50 patients who met the inclusion criteria, 13 (26%) were categorized as responders and 37 (74%) as non-responders. With regard to NAC variables, 12 patients (24%) received cisplatin-based NAC, and 38 patients (74%) received GCb. From the multivariate analysis, pretreatment hemoglobin (Hb) > 12 g/dl (OR 16.42, 95% CI 1.78-151.86, p = 0.01) and neutrophil-to-lymphocyte ratio (NLR) < 3 (OR 12.81, 95% CI 1.36-120.9, p = 0.03) were associated with significantly increased odds of pathologic response, while tumor size < 4 cm (OR 12, 95% CI 1.92-75.05, p = 0.008) was associated with significantly increased odds of pathologic response in the subgroup analysis. Conclusions: Pretreatment Hb and NLR were independently associated with pathologic response to NAC. For MIBC patients who are cisplatin ineligible, GCb followed by RC may be the recommended treatment, particularly in those with tumors less than 4 cm in size. In addition, administering NAC prior to RC does not increase the risk of perioperative complications.